Efeito neuroprotetor de uma proteína isolada de sementes de Morinda citrifolia (noni) na neuropatia sensitiva periférica induzida por oxaliplatina em camundongos - Césario, Francisco Rafael Alves Santana (2023)
The antineoplastic oxaliplatin has a neurotoxic effect a clinical condition called peripheral sensory neuropathy, in which it causes nociceptive, inflammatory, oxidative and morphological changes in nerve cells and compromises the quality of life of patients. McLTP1, a protein isolated from Morinda citrifolia (noni) seeds, from previous studies, has been shown to have an antinociceptive, anti-inflammatory and antioxidant effect in preclinical studies. Therefore, this study sought to investigate the effect of McLTP1 seeds on oxaliplatin-induced PSN in mice. PSN was induced with oxaliplatin injections (2 mg/kg, i.v., 2x/weeks, in total 9 injections) for 28 days in Swiss mice (male, 25-30g). The action of McLTP1 (1, 2 e 4 mg/kg and 4 mg/kg daily) was evaluated, up to the 28th or 56th day (1x/week), through tests of mechanical hyperalgesia (Von Frey test), cold thermal allodynia (acetone test), TRPA1 or TRPM8 involvement, behavioral and motor (Rota rod and Open field test), histology (sciatic nerve), immunofluorescence (c-Fos, ATF-3 and nitrotyrosine), antioxidant (GSH and MDA) in spinal cord or dorsal root ganglion (DRG) and leucometry (count lymphocytes and neutrophils). The results showed that oxaliplatin increased mechanical and thermal nociception, with involvement of TRPA1 and TRPM8, decreased exploratory behavioral activity, promoted nerve tissue damage with leukocyte migration in sciatic nerves, increased the expression of c-Fos, ATF-3 and nitrotyrosine in the spinal cord or DRG, decreased GSH and increased MDA levels in spinal cord and sciatic nerve, and decreased the number of lymphocytes and neutrophils. McLTP1 (4 mg/kg, daily), decreased significantly mechanical and thermal nociception, involved TRPM8, but not TRPA1, did not reverse the reduced exploratory behavioral activity caused by oxaliplatin, decreased nerve tissue damage and leukocyte migration in sciatic nerves, decreased the expression of c-Fos, ATF-3 and nitrotyrosin in the spinal cord or DRG, increased GSH and decreased MDA levels in the sciatic nerve or spinal cord, and prevented the decrease of lymphocytes and neutrophils. It is concluded, therefore, that McLTP1 may exert a neuroprotective role on oxaliplatin-induced PSN, having the participation of the antinociceptive activity, antioxidant and proliferative in leukocytes activity.